Myoxocephalus quadricornis ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Myoxocephalus quadricornis (Linnaeus, 1758). Fourhorn Sculpin. To 36.5 cm (14.4 in) TL (Mecklenburg et al. 2016). Circumpolar; Arctic coasts of Russia to Gulf of Anadyr; Alaska from Beaufort Sea to Saint Lawrence Island, and northern Bristol Bay, Bering Sea (Mecklenburg et al. 2016). Coastal marine and estuarine waters and ascends rivers as far up as 100 km (62 mi) (Mecklenburg et al. 2016); benthic; depth: at least as shallow as 5 m (16 ft) to 55 m (180 ft) (min.: Personal communication: University of Washington, Burke Museum of Natural History and Culture Fish Collection, Seattle, Washington; max.: Mecklenburg et al. 2016). While recognized in the genus Triglopsis by some authors, genetic data supports classification in Myoxocephalus (Mecklenburg et al. 2018). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 123, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...